The idea of a ‘social protection floor’ for South Africa: Developing an approach for social justice and inclusion - Taylor, Viviene (New Agenda: South African Journal of Social and Economic Policy, 2024)
South Africa leads the developing world in building a social protection system. A total of 28 million people — 45% of the population — currently receive a grant, including the nine million who get the Social Relief of Distress grant which has been extended every year since Covid. VIVIENE TAYLOR outlines how the idea of a ‘social protection floor’ developed over the 30 years of democracy and the shortcomings that still delay its full implementation. Over the last 30 years South Africa has established the basis for elements of a “social protection floor”, which should assist even the poorest households to attain a decent standard of living. Achieving a social protection floor is an essential requirement because of historical, political and constitutional imperatives.